Influence of boundary masks on dimensions and surface roughness using segmented exposure in ceramic 3D printing. Issue 3 (15th February 2019) - Wu, Xiangquan; Lian, Qin; Li, Dichen; He, Xiaoning; Meng, Jiali; Liu, Xiaodong; Jin, Zhongmin
Abstract: Mask projection stereolithography can be used to fabricate complex ceramic parts layer by layer through the photopolymerisation of ceramic suspensions. The broadening or lateral overcure of the curing shape occurs because of light scattering effects. Achieving a better dimension and strength quality by adjusting light energy delivery in the boundary mask area has been insufficiently investigated thus far. In this study, the conventional mask was segmented into boundary and interior masks. The exposure time and power of the boundary mask (two pixels wide) were varied to investigate the effects of segmented exposure. The segmented exposure constrained the dimension errors to a width of within two pixels for a feature dimension of less than 1200 µm. It further smoothed the lateral surface of the green part to achieve Ra values of below 6 µm. Moreover, enhancing the boundary mask increased the flexural strength and Weibull modulus to 248 MPa and 11.1, respectively. The results indicate that segmented exposure can potentially be used in complex lattice ceramic structures.